MiR-506 Targets UHRF1 to Inhibit Colorectal Cancer Proliferation and Invasion via the KISS1/PI3K/NF-κB Signaling Axis - Lin, Yilin; Chen, Zhihua; Zheng, Yan; Liu, Yisu; Gao, Ji; Lin, Suyong; Chen, Shaoqin (Frontiers in Cell and Developmental Biology, 2019)
Abstract Background: The UHRF1 gene is an epigenetic modification factor that mediates tumour suppressor gene silencing in a variety of cancers. Related studies have reported that UHRF1 can inhibit the expression of the KISS1 gene. However, the regulatory mechanism underlying UHRF1 expression in colorectal cancer (CRC) is still unclear. The aim of this study was to gain a better understanding of the regulation of UHRF1 expression in CRC and to determine whether it regulates the mechanism by which KISS1 promotes CRC metastasis. Methods: In the present study, the levels of miR-506, UHRF1 and KISS1 expression in CRC tissues and in human CRC cell lines were studied using quantitative real-time PCR (qRT-PCR) and Western blotting. Cell proliferation, migration and invasion assays are used to detect cell proliferation, migration and invasion. A dual-luciferase reporter system was used to confirm the target gene of miR-506. Results: This study found that UHRF1 protein is highly expressed in CRC tissues and negatively correlated with KISS1 protein expression. UHRF1 overexpression activates the PI3K/NF-κB signalling pathway by inhibiting the mRNA expression levels of pathway mediators. Bioinformatics analysis and luciferase reporter gene assays confirmed that miR-506 targets UHRF1. Conclusion: This study identified the regulation of UHRF1 expression in CRC and the mechanism of CRC metastasis. UHRF1 may be a new potential target molecule for future CRC metastasis treatment.